Foreign Policy Attitudes of International Relations Students in Indonesia: Insights from an Inter-Regional Campus Perspective - Jamilah, Maryam; Wardhani, Baiq L (Indonesian Journal of Social Research (IJSR), 2025)
In developing countries like Indonesia, the study of public attitudes toward foreign policy remains a largely unexplored area. As one of the world's largest democracies, public opinion plays an important role in shaping foreign policy, influenced by cultural, historical, economic, and geographical factors. This study aims to examine how International Relations students view it based on the geographical location of their institution. This study uses quantitative approach using SMARTPLS 4 applications. The study population consisted of 431 respondents. Researchers used a measuring instrument namely The Structure of Foreign Policy Attitudes developed by Gravele. The results show different geographic patterns. These findings highlight the role of regional and sociocultural contexts in shaping the foreign policy perspectives of Indonesia's younger generation, providing insight into how Indonesia's diplomatic voice in the future might reflect its geographical and ideological diversity.